Mild Hydrodeoxygenation of Phenols into Cycloalkanes under Ambient Hydrogen Pressure over a Ni/H‐Beta Catalyst. Issue 19 (15th May 2020) - Ohta, Hidetoshi; Sakata, Yoshihiro; Nakanishi, Daisuke; Hayashi, Minoru
Abstract: Hydrodeoxygenation of phenols is an important process for producing six‐membered ring hydrocarbons from lignin. The reaction generally requires high temperatures (300 °C or higher) and high‐pressure H2 gas. In recent years, milder reactions at around 100 °C under atmospheric pressure H2 have been developed by using noble metal catalysts. On the other hand, the reaction with less expensive base metal catalysts still requires either of high temperatures or high‐pressure H2, or the both. Herein, we performed the reaction of various phenols over a Ni/H‐Beta catalyst in octane at 110 °C under atmospheric pressure H2 in a batch reactor to give the corresponding cyclohexanes in 96–33% yield. The reaction proceeds through formation of cyclohexene intermediates, which are eventually converted to cyclohexanes either directly or via transient arene intermediates. Abstract : A Ni catalyst system for the batch‐type hydrodeoxygenation of various phenols under mild conditions was developed. The reaction proceeded by a H‐Beta zeolite‐supported Ni nanoparticle catalyst in octane at 110 °C under ambient hydrogen pressure to yield the corresponding cyclohexanes (8 examples, 96–33% yield). The reaction involves the formation of cyclohexanones, cyclohexanols, cyclohexenes, and arenes as intermediates which are finally converted to cyclohexanes.